2015
DOI: 10.1016/j.immuni.2015.07.018
|View full text |Cite
|
Sign up to set email alerts
|

The PYRIN Domain-only Protein POP1 Inhibits Inflammasome Assembly and Ameliorates Inflammatory Disease

Abstract: SUMMARY In response to infections and tissue damage, ASC-containing inflammasome protein complexes are assembled that promote caspase-1 activation, IL-1β and IL-18 processing and release, pyroptosis, and the release of ASC particles. However, excessive or persistent activation of the inflammasome causes inflammatory diseases. Therefore, a well-balanced inflammasome response is crucial to maintain homeostasis. We show that the PYD-only protein POP1 inhibited ASC-dependent inflammasome assembly by preventing inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
179
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(190 citation statements)
references
References 56 publications
10
179
1
Order By: Relevance
“…30 A20-driven ubiquitination of NLRP3, PYRIN domain-only protein POP1-dependent inhibition of inflammasome assembly, or reactive oxygen species-driven suppression of caspase-1 are just three such regulatory mechanisms. [31][32][33] Figure 2. Inflammasome activation in dendritic cells and macrophages involves numerous elements.…”
Section: Il-1bmentioning
confidence: 99%
“…30 A20-driven ubiquitination of NLRP3, PYRIN domain-only protein POP1-dependent inhibition of inflammasome assembly, or reactive oxygen species-driven suppression of caspase-1 are just three such regulatory mechanisms. [31][32][33] Figure 2. Inflammasome activation in dendritic cells and macrophages involves numerous elements.…”
Section: Il-1bmentioning
confidence: 99%
“…Inhibiting AIM2 inflammasome activity using synthetic inhibitors, such as synthetic Oligodeoxynucleotides (ODN) containing suppressive TTAGGG Motifs (Kaminski et al, 2013) or taking advantage of endogenous AIM2 inhibitors, such as the pyrin-containing proteins, recently described by (Khare et al, 2014;de Almeida et al, 2015), or antimicrobial cathelicidin peptides, reported by Schauber and colleagues , could certainly be explored and studied for their potential to limit undesired inflammation (Man et al, 2016). Still, further research aiming at the discovery of new small-molecules to inhibit AIM2 inflammasome would certainly be of benefit to the development of effective drugs to treat chronic diseases, in which inflammation is the key player.…”
Section: Therapeutic Implications Of Aim2 Inflammasomementioning
confidence: 99%
“…In this issue of Immunity, de Almeida et al (2015) report that the PYRIN domain-only protein (POP1) efficiently inhibits inflammasome activation, identifying it as a pan-inflammasome inhibitor.…”
mentioning
confidence: 99%
“…In the article by de Almeida et al (2015) appearing in this issue of Immunity, the authors have identified PYRIN (PYD) only protein (POP1) as a negative regulator of inflammasome activation. Although the POP family of proteins was identified in humans more than 10 years ago (they are not found in mice) and includes POP1 (also known as ASC2), POP2, POP3, and POP4 (Stehlik et al, 2003), their functions have been unclear.…”
mentioning
confidence: 99%
See 1 more Smart Citation